2008
DOI: 10.1073/pnas.0801567105
|View full text |Cite
|
Sign up to set email alerts
|

ALIX-CHMP4 interactions in the human ESCRT pathway

Abstract: The ESCRT pathway facilitates membrane fission events during enveloped virus budding, multivesicular body formation, and cytokinesis. To promote HIV budding and cytokinesis, the ALIX protein must bind and recruit CHMP4 subunits of the ESCRT-III complex, which in turn participate in essential membrane remodeling functions. Here, we report that the Bro1 domain of ALIX binds specifically to C-terminal residues of the human CHMP4 proteins (CHMP4A-C). Crystal structures of the complexes reveal that the CHMP4 C-term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
252
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(262 citation statements)
references
References 56 publications
10
252
0
Order By: Relevance
“…CHMP4A and CHMP4B (which was identified in the screen; Fig. 2) are known to interact with ALIX and CHMP7 (22,23), and our previous RNAi depletion studies demonstrated that VPS4B is essential for eHAV biogenesis (2). Notably, however, antibody to TSG101, an ESCRT-I-associated protein that unlike ALIX and VPS4B is not required for eHAV biogenesis (2), failed to precipitate eHAV.…”
Section: Resultsmentioning
confidence: 98%
“…CHMP4A and CHMP4B (which was identified in the screen; Fig. 2) are known to interact with ALIX and CHMP7 (22,23), and our previous RNAi depletion studies demonstrated that VPS4B is essential for eHAV biogenesis (2). Notably, however, antibody to TSG101, an ESCRT-I-associated protein that unlike ALIX and VPS4B is not required for eHAV biogenesis (2), failed to precipitate eHAV.…”
Section: Resultsmentioning
confidence: 98%
“…The bro1-domain was first identified in the ESCRT pathway member Bro1 as a Snf7-interaction domain. (Kim et al 2005;McCullough et al 2008). As both Bro1 and Rim20 act as scaffold proteins, Bro1 and Rim20 have been proposed to act as adaptors, promoting downstream Snf7 function toward the ESCRT pathway or the Rim101 pathway, respectively (Boysen and Mitchell 2006).…”
mentioning
confidence: 99%
“…It has not yet been clarified whether this is the case in mammals. The ESCRTs' were found to have a beneficial role in innate immunity by restricting microbial growth and infection (von Schwedler et al, 2003;Vieira et al, 2004;Philips et al, 2008;Morita & Sundquist, 2004;Martin-Serrano & Marsh, 2007;McCullough et al, 2008). The ESCRTs' however, are turned against the host in viral infections.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have now shown that these host cell pathways can be manipulated by viruses and microorganisms in order to facilitate infection (von Schwedler et al, 2003;Vieira et al, 2004;Philips et al, 2008;Morita & Sundquist, 2004;Martin-Serrano & Marsh, 2007;McCullough et al, 2008). ESCRTs' play an important role in degenerative endosomal trafficking, so it is not surprising that they are involved in killing many microorganisms.…”
Section: Microbial Infectionsmentioning
confidence: 99%